Testing the prediction profiler with disallowed combinations—A statistical engineering case study. Issue Volume 34:Issues 4(2022) (29th November 2022) - Ash, Jeremy; King, Caleb; Lancaster, Laura; Lekivetz, Ryan; Morgan, Joseph; Saanchi, Yeng
Abstract: The prediction profiler is an interactive display in JMP statistical software that allows a user to explore the relationships between multiple factors and responses. A common use case of the profiler is for exploring the predicted model from a designed experiment. For experiments with a constrained design region defined by disallowed combinations, the profiler was recently enhanced to obey such constraints. In this case study, we show how our validation approach for this enhancement touched upon many of the fundamental principles of statistical engineering. The team approached the task as a design of experiments problem.